Breast fibroadenoma: diagnostic performance of gray-scale sonography and sonoelastography: a prospective observational study - Phatak, Suresh; Gupta, Nipun (International Journal of Research in Medical Sciences, 2017)
Background: Elastography is a new technique that can be especially helpful when used as an adjunct to conventional B-mode ultrasound in evaluating breast lesions. The aim of this study was to evaluate the diagnostic performance of interpretation criteria for conventional sonography and sonoelastography in characterising fibroadenoma breast with pathological correlation. Methods: 50 breast fibroadenomas were prospectively evaluated by ultrasound as well as by strain elastography followed by FNAC//Histopathology correlation. The criteria used in breast elastography were Elastography Score and Strain Ratio. The sensitivity, specificity, accuracy, positive predictive value and negative predictive value were calculated for each modality. Results: The elastography score was found to have the best performance among the 2 criteria used with a sensitivity, specificity and accuracy of 95.83%, 50% and 94% respectively. Conclusions: While conventional ultrasound remains the primary modality for the characterization of breast masses, elastography has the potential to improve the sensitivity, specificity and accuracy of conventional ultrasound and, thus avoiding unnecessary biopsy.